579. Design and Immunogenicity of a Pan-SARS-CoV-2 Synthetic DNA Vaccine. (4th December 2021) - Schultheis, Katherine; Reed, Charles C; Andrade, Viviane M; Kalia, Richa; Tur, Jared; Schouest, Blake; Elwood, Dustin; Maricic, Igor; Doan, Arthur; Eblimit, Zeena; Pezzoli, Patrick; Amante, Dinah; et al.
Abstract: Background: First-generation COVID-19 vaccines are matched to spike protein of the Wuhan-H1 (WT) strain. Convalescent and vaccinee samples show reduced neutralization of SARS-CoV-2 variants of concern (VOC). Next generation DNA vaccines could be matched to single variants or synthetically designed for broader coverage of multiple VOCs. Methods: The synthetic consensus (SynCon®) sequence for INO-4802 SARS-CoV-2 spike with focused RBD changes and dual proline mutations was codon-optimized (Figure 1). Sequences for wild-type (pWT) and B.1.351 (pB.1.351) were similarly optimized. Immunogenicity was evaluated in BALB/c mice. Pre-clinical efficacy was assessed in the Syrian Hamster model. Figure 1. Design Strategy for INO-4802 Results: INO-4802 induced potent neutralizing antibody responses against WT, B.1.1.7, P.1, and B.1.351 VOC in a murine model. pWT vaccinated animals showed a 3-fold reduction in mean neutralizing ID50 for the B.1.351 pseudotyped virus. INO-4802 immunized animals had significantly higher (p = 0.0408) neutralizing capacity (mean ID50 816.16). ID50 of pB.1.351 serum was reduced 7-fold for B.1.1.7 and significantly lower (p = 0.0068) than INO-4802 (317.44). INO-4802 neutralized WT (548.28) comparable to pWT. INO-4802 also neutralized P.1 (1026.6) (Figure 2). pWT, pB.1.351 or INO-4802 induced similar T-cell responses against all variants. INO-4802 skewed towards a TH1-response. All hamsters vaccinated with INO-4802 or pB.1.351 were protected from weight loss after B.1.351 live virus challenge. 4/6 pWT immunized hamsters were completely protected. pWT immunized hamsters neutralized WT (1090) but not B.1.351 (39.16). INO-4802 neutralized both WT (672.2) and B.1.351 (1121) (Figure 3). We observed higher increase of binding titers following heterologous boost with INO-4802 (3.6 – 4.4 log2-fold change) than homologous boost with pWT (2.0 – 2.4 log2 fold change) (Figure 4). Figure 2. INO-4802 Induces Functional Humoral Immune Response Against SARS-CoV-2 Variants of Concern Figure 3. INO-4802 Protects Hamsters Against Challenge With B.1.351 Live Virus Figure 4. Heterologous Boost with INO-4802 Induces Humoral Immune Response Against SARS-CoV-2 Variants Conclusion: Vaccines matching single VOCs, like pB.1.351 and pWT, elicit responses against the matched antigen but have reduced cross-reactivity. Presenting a pan-SARS-CoV-2 approach, INO-4802 may offer substantial advantages in terms of cross-strain protection, reduced susceptibility to escape mutants and non-restricted geographical use. Disclosures: Katherine Schultheis, MSc, Inovio Pharmaceuticals (Employee) Charles C. Reed, PhD, Inovio Pharmaceuticals (Employee, Shareholder) Viviane M. Andrade, PhD, Inovio Pharmaceuticals Inc. (Employee) Richa Kalia, MS, Inovio Pharmaceuticals (Employee, Other Financial or Material Support, I have stock options with Inovio Pharmaceuticals as an employee.) Jared Tur, PhD, Inovio (Employee) Blake Schouest, PhD, Inovio Pharmaceuticals (Employee) Dustin Elwood, PhD, Inovio Pharmaceuticals (Employee) Arthur Doan, n/a, Inovio (Employee) Patrick Pezzoli, BS, Inovio (Employee) Dinah Amante, BS, Inovio (Employee) David Weiner, PhD, Inovio (Board Member, Grant/Research Support, Shareholder, I serve on the SAB in addition to the above activities) J Joseph Kim, PhD, Inovio (Employee) Laurent Humeau, PhD, Inovio Pharmaceuticals (Employee) Stephanie Ramos, PhD, Inovio Pharmaceuticals (Employee) Trevor R. F. Smith, PhD, Inovio (Employee, Shareholder) Kate Broderick, PhD, Inovio (Employee).